Assessment of young learners' foreign language in Slovenian primary schools - Brumen, Mihaela (ELOPE (Ljubljana), 2005)
Assessment should regularly and systematically be integrated into the process of learning and teaching. That is, it should reflect the kinds of activity that regularly occur in class and with which pupils are famillar. It should have a strong diagnostic function that will provide useful information to teachers and learners in enabling them to take stock of where they are and if necessary to adapt their particular strategies. The research reported in this article focuses on an investigation of Slovenian foreign language teachers' experiences and attitudes toward the assessment of primary learners of a foreign language. By means of a survey questionnaire we present the characteristics of teachers' assessment in practice, and teachers' attitudes toward assessment at the primary level. The survey shows that all teachers assess their young learners of foreign languages, more often numerically than with comments. They also believe that they are responsible for assessment, just as they believe that teachers and young learners alike have the right to these the results.
Keywords: izobraževanje; ocenjevanje znanja; osnovne šole; preverjanje znanja; tuji jeziki; začetni pouk